The Adaptation of Building Information Modelling (BIM) on Multipurpose Building in Johor Matriculation College Architectural Plan for Future Engineering Reference - Tan, Wan Yi; DR Muhammad Nizam Bin Zakaria (Recent Trends in Civil Engineering and Built Environment, 2021)
Building Information Modeling (BIM) is a process involved in planning, designing, building, operation and maintenance, which is rapidly growing worldwide for improvement in the field of architecture, engineering, and construction (AEC). The development of BIM is often implemented for new buildings. Meanwhile, most of the existing structures are not preserved, renovated or deconstructed with BIM yet. The purpose of this study is to contribute for future engineer reference by providing the information and data in the work of maintenance, renovation and demolition on the building in future. In this research, the analysis of the existing building structure in Johor Matriculation College was conducted to obtain the 3D modeling from BIM approaches. Regarding the studies from review of literature, the BIM tools implemented in this research is Tekla Structural Designer (TSD), which is to structurally analyze and design the existing building structure in accordance to Eurocode Standard, meanwhile Autodesk Revit is to create an information-rich 3D model of the facilities. The adaptation of BIM in this model designing requires Level of Development (LOD) to reach LOD 300: Design Development. This study also compares the design results obtained from design software with the manual calculation of the existing as-built drawing to justify that BIM techniques can be accomplished for existing facilities with accurate data produced. In summary, this research has been proven that BIM tends to provide efficiency and accuracy along the project lifecycle in construction firm, according to the conceptual design, visualization, and analysis of the structure.